Patients with cancer: social representations in nursing - Oliveira, A.; Correia, F.; Sá, C. (Mediterranean Journal of Social Sciences, 2015)
The meaning attributed to cancer, when passing the patient-family boundary is, in some degree, also shared between health professionals, which can have effect on the professionals’ performance and influence the opinions of users about health services. The focus of this work is the analysis of social representations about patients with cancer, in a population of nurse students, professional nurses working with cancer patients, and professional nurses not working with cancer patients, of both sexes. Our main goal is to know their conceptions towards oncologic patients. The methodological option was the social representations theory. The data was retrieved by questionnaire using the free word association technique. Several Factorial Correspondence Analysis where made to identify the different dimensions (or dependent variables). In general, all professional groups represent oncologic patients by their physical alterations. Nurse students decipher cancer in a distant perspective, as the unknown and something that causes discomfort and eventually… death. In fact, patients with cancer are strongly associated to situations of pain, involving suffering, and death. Women show a more positive perception of cancer, supported in treatment and hoping for a healing possibility. Men demonstrate a greater difficulty in dissociating the patients with cancer of people who soon will die. There is still a long way to walk before cancer patients are no longer associated to a death sign.